Sedação em medicina intensiva: uso de remifentanil na prática clínica - Leal, Patrícia Helena Da Rocha [UNIFESP] (2006)
BACKGROUND AND OBJECTIVES: Critically ill patients frequently need to use sedative and analgesic drugs, as part of their treatment or during several procedures. It is a challenge for all intensive care providers to determine the best drug to be used for each patient, with less collateral effects. The objective of this study is to describe the background to give the use of remifentanil in intensive care clinical practice. CONTENTS: Remifentanil is a short acting opioid agonist little used in intensive care medicine. Several studies have been published, showing that remifentanil is a safe drug to be used for the sedation and analgesia for intensive care patients, still needing more information regardless to septic shock patients. CONCLUSIONS: Because remifentanil is a relatively new drug, it is not yet part of the routine drugs used for intensive care providers, although solid evidences of its safety and efficiency for critically ill patients.